1993
DOI: 10.1111/j.1365-2923.1993.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of context and preferred learning environments: approaches to studying physiology

Abstract: One hundred and twenty-eight medical students who had experienced a traditional-style preclinical curriculum completed three self-report questionnaires. Using factor analysis of students' responses this study explores interactions between study orientation, preferences for different kinds of learning environment, and evaluations of the physiology course. Such interactions can provide insight into the reasons why students fail to adopt effective learning strategies. Although many students had the intention to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The other studies did not find significant correlations, two of which have small sample size, hence may have lacked the power to find significant differences (Elam et al 1999;de Bruin et al 2005). Tan and Thanaraj (1993) found significantly negative correlation, but in this study intrinsic motivation was measured with only one item in the questionnaire. We were not always able to confirm the reliability of the outcome measures, so these findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The other studies did not find significant correlations, two of which have small sample size, hence may have lacked the power to find significant differences (Elam et al 1999;de Bruin et al 2005). Tan and Thanaraj (1993) found significantly negative correlation, but in this study intrinsic motivation was measured with only one item in the questionnaire. We were not always able to confirm the reliability of the outcome measures, so these findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 89%
“…No significant difference was found in performance between students with high and low motivation (conditions created by using external motivators) and controls when tested on clinical case processing and recall of differential diagnosis (de Bruin et al 2005). Intrinsic motivation, which was measured by only one item, was found to be significantly negatively correlated (r ¼ À0.17) with academic success (Tan & Thanaraj 1993).…”
Section: Motivation As An Independent Variablementioning
confidence: 96%
“…Although we cannot determine causation from this study, studies of undergraduate students indicate that the learning environment affects the approach to learning, independent of the preferred learning style. 7 1517 Yet medical students with a deep approach to learning were more likely to take an intercalated degree and pursue a career in research or laboratory medicine, indicating that their approach to learning may affect the environment they choose 18…”
Section: Discussionmentioning
confidence: 99%
“…If they are put under undue pressure to complete tasks within limited timeframes, or are presented with a syllabus that emphasises coverage and high contact hours, superficial approaches to learning are a predictable outcome. Tan and Thanaraj (1993) pointed out that in the absence of sufficient time to grapple with complex ideas, crammed curricula could lead to the simplification of concepts by students and a fear of failure that might prompt the avoidance of difficult tasks. Further, they suggested that the same demanding curriculum might force students to seek more strategic approaches to studying, focused on securing examination success.…”
Section: Contextualising Approaches To Learningmentioning
confidence: 99%